Preparation and Characterization of Nanomicelle for Ocular delivery of fluoroquinolone derivative - Singh, Pawan; Verma, Navneet (Journal of Drug Delivery and Therapeutics, 2019)
Pluronic nanomicelles were prepared for Ocular delivery by incorporation of methyl alcohol as a dispersing agent and the surface was modifying by chitosan to improve the bioavailability. Nanomicelle dispersed well in solution and having a core shell-like structure with particle range from 100-350 nm and zeta potential between 5.45mV -18.98mV indicating very suitable use as an ophthalmic carrier. The turbidity test reveals that the prepared nanomicelle were very stable under simulated tear fluid environment and simulated tear fluid, which prevent the blurred vision. The drug entrapment of ciprofloxacin hydrochloride in nanomicelle was too much high 98.07±6.8040. Finally, the drug release indicates the Pluronic nanomicelle modify by chitosan have sustained release behavior. As a result of Pluronic-Chitosan nanomicelle system provide a potential opportunity in decreasing dosing frequency of administration and improving patient compliance for ocular drug delivery.Keywords: Chitosan, Nanomicelle, Ocular delivery system, Poloxamer 407.